Can aged Camellia oleifera Abel oil truly be used to treat atopic dermatitis? - Ouyang, Xi-Lin; Yuan, Zhang-Lin; Chen, Xiao-Bing; Gan, Hong-Wan; Guo, Sen-Hui; Cai, Juan; Zhong, Jing-Jing (Frontiers in Pharmacology, 2024)
Atopic dermatitis is an inflammatory skin condition characterized by erythema, eruption, lichenification, and pruritus. Aged Camellia oleifera Abel oil, an effective empirical plant oil utilized by the Gannan Hakka people in China to alleviate the symptoms of atopic dermatitis. However, no scientific studies have been reported to prove whether this oil is truly effective. We conducted this study to confirm whether aged C. oleifera oil could alleviate the symptoms of 2,4dinitrochlorobenzene-induced atopic dermatitis in mice. Differences in the thickness and weight of the right and left ears were measured. ELISA was used to determine the serum levels of the inflammatory factors IL-4, IgE, IFN-γ, and TNF-α. HE staining was performed to observe inflammatory cell infiltration in the mouse skin lesions. In addition, the metabolites of aged C. oleifera oils were analyzed, and molecular docking was used to assess the binding affinity of the major metabolites to filaggrin, a protein involved in skin barrier function. Animal studies showed that aged C. oleifera oil significantly improved the symptoms of atopic dermatitis. HE staining and measurement of inflammatory factor levels revealed similar results. A total of 41 metabolites were tentatively identified in the oil, with fatty acids emerging as the major metabolites. Molecular docking confirmed that the three most abundant fatty acids, i.e., oleic acid, n-hexadecanoic acid, and octadecanoic acid, bind well to filaggrin. Our results suggest that aged C. oleifera oils can be used to ameliorate the symptoms of atopic dermatitis. Fatty acids may be the major active metabolites responsible for the observed therapeutic effects by reducing transdermal water loss, increasing skin hydration, alleviating DNCB-induced skin barrier alterations, and eliminating itchy scratching caused by dry skin.